(untitled) (Journal of Science and Technology, 2016)
The proper selection and application of refractory products requires a good knowledge of their high temperature deformation behaviour as a function of time and stress. Resistance to creep failure, an important performance criterion, has been evaluated for Nib’. Ghana! Kaolin clay bodies using the Netzsch Furnace. During the test thermal expansion was steady until a temperature of th45`C’ at which point a maximum dilation of 0.29% was recorded. The heat treatment continued, after the maximum dilation, until the furnace attained a soak temperature of 4280r. Heating over an extended time period at elevated temperatures was carried out to allow the various stages of creep, i.e., the initial elastic extension through primary and secondary creep to the tertiary creep level, to be monitored. The per cent deformation (creep) and creep rate recorded between the 2001 and 50th hours of heating, which is an important indicator of the load bearing capacity of refractory bodies was found to be 0.241% and 0.009%hr respectively.